Evaluasi Profesionalisme Guru Dalam Pembelajaran Di SMPN 3 Bajeng Kabupaten Gowa - Risna; Azizah, Nur; Rahmi, Nur; Mukramin, Sam'un (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2023)
Abstrack In the world of Indonesian education, there are many teachers or educational staff, but not many teachers know how professional teachers perform. Teachers have a very important position in the community environment, both at school and in the community. Teachers play an important role in improving the quality of education, apart from having high knowledge in the substance of the subject area. Professional teacher learning is a determining factor in a quality educational process, so to improve learning and to improve the quality of learning, teacher professionalism must be increased. The aim of this research is to see how professionalism teachers are in learning at SMPN 3 Bajeng. The research method uses the interview method as qualitative research. The results of this research show that the professionalism of teachers in learning at SMP 3 Bajeng is professional, this is because the teachers have been certified and the school has made several efforts to increase teacher professionalism. Even though there are still some teachers who are not yet professional or are still teaching not according to their field or expertise because the subject teachers are still limited and not yet certified, the school will still make efforts so that the teachers at the school will become professional teachers. Abstrak Dunia pendidikan Indonesia banyak guru atau tenaga pendidik, namun tidak banyak guru mengetahui bagaimanah kinerja guru professional, guru memiliki posisi yang sangat penting dalam lingkungan masyarakat baik disekolah maupun masyarakat guru memegang peranan penting dalam peningkatan mutu pendidikan,selain memiliki pengetahuan yang tinggi dalam substansi bidang mata pelajaran guru yang profesional merupakan faktor penentu proses pendidikan yang berkualitas dengan itu untuk melakukan perbaikan pembelajaran dan untuk meningkatkan kualitas dalam pembelajaran maka harus meningkatkan profesionalisme guru .Tujuan penelitian ini untuk melihat bagaimanah profesionalisme guru dalam pembelajaran di SMPN 3 Bajeng.Metode penelitian menggunahkan metode wawancara sebagai penelitian kualitatif. Hasil penelitian ini menunjukkan bahwa profesionalisme guru dalam pembelajaran di SMP 3 Bajeng telah profesional hal ini karna guru-guru tersebut telah bersertifikasi dan sekolah tersebut telah melakukan beberapa upaya-upaya untuk meningkatkan profesionalisme guru. Meski masih ada beberapa guru yang belum profesional atau masih mengajar tidak sesuai bidangnya atau keahlian disebabkan guru mata pelajaran juga masih terbatas dan belum bersertifikasi sekolah akan tetap berupaya agar guru-guru disekolah itu akan menjadi guru profesional.